Graham Towers and his times : a biography - Fullerton, Douglas H. (Toronto, Ont. : McClelland and Stewart, 1986)
This biography of Graham Towers was written to mark the Bank of Canada's fiftieth birthday.
Includes index.
Includes bibliographical references: p. 320-341.
ucj 18/01/2019
Loans
Keywords: Towers, Graham F; Bankers